Results of a Survey of Simulation Software and Decision Support Tools in use in Australian Higher Education. - Fife, Ray L. (Australian Learning and Teaching Council (ALTC), 2010)
Report presenting the results of a survey of simulation software and decision support tools in use in Australian higher education. The survey was conducted as part of a project investigating a technological solution to support enhanced e-learning and teaching performance with the aim of producing graduates with better workplace competencies. The project aimed to create a system implementation protocol that would deliver a range of licensed simulation software across the sector, and collaborate with key industries to gain access to sector-relevant simulation tools that would otherwise be cost-prohibitive to acquire for single students or single institutions. The project involved: (1) Identification of and recommendations for resolution of technical issues, (2) audit of software available among participating institutions, and recommendations for additional software as necessary, (3) draft IP agreement, (4) draft MoU based on the implementation protocol, (5) decision-making tool/checklist to assist potential users of the system to assess the adequacy/suitability of their hardware/software and identity management system for interfacing to the shared DST system, and (6) overview of the structure for an interface to the learning management systems commonly used in the higher education sector.